Conflicts in Counseling LGBT Clients: Recommendations in Increasing Muslim Counselors' Competency - Syed Mahmood, Syarifah Rohaniah; Ssekamanya, Siraje Abdallah (Persatuan Kaunseling Syarie, 2020)
A phenomenological method of inquiry was used to understand the conflicts experienced by Muslim counsellors in counselling LGBT clients. In-depth interviews were conducted with six Muslim counsellors at Public Institutions of Higher Education (PIHE) in Peninsular Malaysia. Due to lack of knowledge, clinical experiences and training in counselling LGBT clients, they experienced three types of value conflicts: conflicting goals, conflicting roles and conflicting interests. Thus, this paper offers recommendations to the parties involve in providing training and accreditation to counsellors in Malaysia: counsellor education programs, Malaysian Board of Counsellors and Perkama International.